Origin of Electron Boomerang Stripes: Statistical Study. Issue 11 (9th June 2021) - Zhao, X. X.; Hao, Y. X.; Zong, Q.‐G.; Zhou, X.‐Z.; Yue, C.; Chen, X. R.; Liu, Y.; Liu, Z.‐Y.; Blake, J. B.; Claudepierre, S. G.; Reeves, G. D.
Abstract: In the outer radiation belt, localized ultralow frequency (ULF) waves can interact with energetic electrons by drift resonance, leading to quasiperiodic oscillations. The oscillations in the pitch angle spectrum can be characterized by either boomerang‐shaped or straight stripes. Previous studies have shown that boomerang‐shaped stripes evolve from straight ones when electrons drift away from the localized wave interaction region. Based on the time‐of‐flight technique on the pitch angle‐dependent drift velocity, the origin can be remotely identified from the pitch angle dispersion. We report 27 straight stripe events and 86 boomerang‐shaped events observed by Van Allen Probes from January 1, 2013, to December 31, 2017. Statistical study shows a good coincidence between the locations of straight ones and traceback regions from boomerang‐shaped ones. These locations, mainly located in noon‐to‐dusk region, coincide well with the plasmaspheric plumes. Thus, localized ULF waves trapped in the plume may result in the preference of localized ULF wave‐electron interactions at noon‐to‐dusk region. Plain Language Summary: In the outer radiation belt, energetic electrons drift eastward with periods from minutes to hours, which coincide with ultralow frequency (ULF) waves. Thus, drift resonance can efficiently exchange energy between ULF waves and energetic electrons. Previous studies present that drift resonances can result in either straight or curved quasiperiodic stripes on the electron pitch angle (the angle between electron velocity and magnetic field) distributions. Curved stripes are thought to evolve from vertical ones due to the pitch angle‐dependence of drift velocities. Based on the time‐of‐flight technique, one can trace back from the curved stripes to the time and location of the expected straight ones, at which the drift‐resonant interaction takes place. In this study, we find 27 straight stripes and 86 curved stripes events observed by Van Allen Probes from 2013 to 2017. The traceback regions from these curved stripes events are mainly located at the noon to the duskside, coinciding with the locations of straight stripe events. These results suggest that the drift resonance between the localized ULF waves and energetic electrons occurs more frequently from the noon to the duskside. Most source regions coincide with the plasmaspheric plume, suggesting localized ULF waves are trapped in the plume. Key Points: From 2013 to 2017, 86 "boomerang‐shaped" and 27 straight stripe events on electron PADs have been found from Magnetic Electron Ion Spectrometer observations Traceback regions from "boomerang‐shaped" events coincide with the locations of straight ones, suggesting the evolution due to drift motion Origins of both kinds of events are mainly located at noon‐to‐dusk region, suggesting preferential ultralow frequency wave‐electron drift resonance therein